A framework for mapping the distribution of seabirds by integrating tracking, demography and phenology. Issue 3 (4th February 2020) - Carneiro, Ana P. B.; Pearmain, Elizabeth J.; Oppel, Steffen; Clay, Thomas A.; Phillips, Richard A.; Bonnet‐Lebrun, Anne‐Sophie; Wanless, Ross M.; Abraham, Edward; Richard, Yvan; Rice, Joel; Handley, Jonathan; Davies, Tammy E.; et al.
Abstract: The identification of geographic areas where the densities of animals are highest across their annual cycles is a crucial step in conservation planning. In marine environments, however, it can be particularly difficult to map the distribution of species, and the methods used are usually biased towards adults, neglecting the distribution of other life‐history stages even though they can represent a substantial proportion of the total population. Here we develop a methodological framework for estimating population‐level density distributions of seabirds, integrating tracking data across the main life‐history stages (adult breeders and non‐breeders, juveniles and immatures). We incorporate demographic information (adult and juvenile/immature survival, breeding frequency and success, age at first breeding) and phenological data (average timing of breeding and migration) to weight distribution maps according to the proportion of the population represented by each life‐history stage. We demonstrate the utility of this framework by applying it to 22 species of albatrosses and petrels that are of conservation concern due to interactions with fisheries. Because juveniles, immatures and non‐breeding adults account for 47%–81% of all individuals of the populations analysed, ignoring the distributions of birds in these stages leads to biased estimates of overlap with threats, and may misdirect management and conservation efforts. Population‐level distribution maps using only adult distributions underestimated exposure to longline fishing effort by 18%–42%, compared with overlap scores based on data from all life‐history stages. Synthesis and applications . Our framework synthesizes and improves on previous approaches to estimate seabird densities at sea, is applicable for data‐poor situations, and provides a standard and repeatable method that can be easily updated as new tracking and demographic data become available. We provide scripts in the R language and a Shiny app to facilitate future applications of our approach. We recommend that where sufficient tracking data are available, this framework be used to assess overlap of seabirds with at‐sea threats such as overharvesting, fisheries bycatch, shipping, offshore industry and pollutants. Based on such an analysis, conservation interventions could be directed towards areas where they have the greatest impact on populations. Abstract : Our framework synthesizes and improves on previous approaches to estimate seabird densities at sea, is applicable for data‐poor situations, and provides a standard and repeatable method that can be easily updated as new tracking and demographic data become available. We provide scripts in the r language and a Shiny app to facilitate future applications of our approach. We recommend that where sufficient tracking data are available, this framework be used to assess overlap of seabirds with at‐sea threats such as overharvesting, fisheries bycatch, shipping, offshore industry and pollutants. Based on such an analysis, conservation interventions could be directed towards areas where they have the greatest impact on populations. Translated Abstract Resumen: La identificación de áreas geográficas donde las densidades de animales son más altas de acuerdo a sus ciclos anuales es un paso crucial en la planificación de la conservación. Sin embargo, en ambientes marinos, puede ser particularmente difícil mapear la distribución de especies, y los métodos utilizados generalmente están sesgados hacia los adultos, sin tener en cuenta la distribución de individuos en otras etapas de su ciclo de vida que pueden representar una proporción sustancial de la población total. Aquí desarrollamos una metodología para estimar las densidades a nivel de población de aves marinas, integrando datos de seguimiento para todas las etapas principales de su ciclo de vida (adultos reproductores y no reproductores, juveniles e inmaduros). Incorporamos información demográfica (supervivencia de adultos y juveniles/inmaduros, frecuencia y éxito de reproducción, edad en la primera reproducción) y datos fenológicos (tiempo promedio de reproducción y migración) para ponderar los mapas de distribución de acuerdo con la proporción de la población representada por cada etapa de vida. Demostramos la utilidad de esta metodología al aplicarla a 22 especies de albatros y petreles que se encuentran muchas veces amenazados debido a las interacciones con las pesquerías. Debido a que los juveniles, los inmaduros y los adultos no reproductores representan el 47%–81% de todos los individuos de las poblaciones analizadas, ignorar la distribución de las aves en estas etapas lleva a estimaciones sesgadas del solapamiento de estas aves con amenazas, y puede conducir a esfuerzos de conservación y manejo erróneos. Los mapas de distribución a nivel de población que usan solo distribuciones de adultos subestimaron la exposición al esfuerzo de pesca con palangre en un 18 al 42%, en comparación con el solapamiento estimado utilizando datos de todas las etapas de vida. Síntesis y aplicaciones. Nuestro método sintetiza y mejora los enfoques anteriores para estimar las densidades de aves marinas en el mar, incluso en situaciones de escasez de datos, y proporciona una metodología estándar y repetible que se puede actualizar fácilmente a medida que se disponga de nuevos datos demográficos y de seguimiento. Proporcionamos scripts en el lenguaje R y una aplicación Shiny para facilitar futuras aplicaciones de nuestro enfoque. Recomendamos que, cuando haya suficientes datos de seguimiento disponibles, este método se utilice para evaluar el solapamiento de las aves marinas con sus amenazas en el mar, como la sobreexplotación pesquera, la captura incidental de la pesca, el transporte marítimo, la industria en alta mar y los contaminantes. Con base en dicho análisis, las intervenciones de conservación podrían dirigirse hacia áreas que tengan el mayor impacto en las poblaciones.